Improving the methodological foundations of lending to manufacturing enterprises in Uzbekistan - Khasanov Shamsiddin Khafizovich, (THE INNOVATION ECONOMY, 2026)
This article provides a comprehensive analysis of the scientific and methodological foundations for improving the lending system of manufacturing enterprises in Uzbekistan. The economic essence of the lending process, its role in expanding production capacity, and its impact on financial stability are highlighted. The paper examines the current credit policy, interest rates, collateral mechanisms, and the efficiency of using credit resources. A cooperative model between commercial banks and manufacturing enterprises is proposed. The author has developed a differentiated approach to lending, taking into account the specific characteristics of industrial sectors. The research findings indicate that targeted allocation of credit resources and the strengthening of monitoring mechanisms have a positive impact on economic growth. Based on international experience, methodological recommendations for reducing credit risks and improving the investment environment are proposed. The results of this study serve to further enhance the financial support system for manufacturing enterprises.